Effect of genotypes and aflatoxin levels in the diets on early laying characteristics of local ducks - Prasetyo, L. Hardi; Susanti, T (Indonesian Animal Sciences Society, 2010)
Layer ducks are known for their sensitivity to aflatoxin contamination in their diets, and this has been causing problem in egg productivity of local ducks due to feeding system practiced by traditional farmers. This study was aimed at exploring the level of sensitivity of Mojosari and Tegal ducks to different aflatoxin levels in their diets, especially on characteristics during early laying period. Three hundreds and nine female Mojosari ducks and 260 female Tegal ducks were used in this study. Two levels of aflatoxin in the diets, 0 and 150 ppb, were given to 4 week-old ducklings for 4 weeks. Observations were taken on age at first laying, body weight at first laying, and egg qualities as early indications of the egg production potentials. The results showed that different levels of aflatoxin in the diets only affected live weight at first laying, and not age at first laying. The two genotypes differed significantly in egg weight, yolk weight, and shell weight. It is concluded that aflatoxin contamination in the diets during early growth did not really affect characteristics of early laying of Mojosari and Tegal ducks. Key Words: Local Ducks, Aflatoxin